Chemoradiation Therapy Sequencing for Resected Pancreatic Adenocarcinoma in the National Cancer Data Base - Colbert, Lauren E. (Cancer, 2014)
BACKGROUND: Pancreatic adenocarcinoma (PAC) has low overall survival (OS) rates and high recurrence rates following surgical resection. The role for preoperative radiation therapy (prRT) for PAC versus postoperative RT (poRT) remains uncertain. The authors used the National Cancer Data Base (NCDB) to report prRT outcomes for the largest multi-institutional patient cohort to date. METHODS: NCDB data were obtained for all patients who underwent resection and external beam radiation (RT) for PAC from 1998-2002. Patients with metastatic (M1) disease, intraoperative RT, RT both before and after surgery, missing OS or missing RT variables were excluded. Univariate (UV) and Multivariate (MV) analysis were run using treatment characteristics, tumor characteristics and patient demographics. The difference in patients’ known characteristics was described by a Chi-square test or ANOVA. RESULTS: 5414 patients were identified. 277 received prRT and 5137 received poRT. Overall, 92.9% received chemotherapy and 7.1% received RT alone. 56% (2990/5307) of patients were AJCC 5(th) ed. stage III. Median tumor size was 3 cm (range: 0-9.9). 82% (199/244) of prRT patients had negative surgical margins; 72% (3383/4699) of poRT patients had negative margins. 41% (71/173) of prRT were lymph node (LN) positive; 65% (3159/4833) of poRT were LN positive. Median OS for prRT patients was 18 months (95% CI 18-19) and for poRT patients, 19 months (95% CI 17-22). CONCLUSIONS: PrRT was associated with lower stage, higher rates of negative margins and lower rates of lymph node positivity at resection. However, there was no significant difference in median OS versus the poRT group.